Design the Balance of System of Photovoltaic for Low Load Application - Y.M. Irwan; Z. Syafiqah; A.R. Amelia; M. Irwanto; W.Z. Leow; S. Ibrahim (Institute of Advanced Engineering and Science, 2016)
This paper presents an alternative method to reduce the monthly electricity bill at Centre of Excellence for Renewable Energy (CERE) which is by installing a stand-alone photovoltaic (PV) system. In the stand-alone PV system, apart from the PV module and loads, other components in the system such as battery, charge controller, inverter and protection device are categorized under Balance of System (BOS) component. In order for the loads to receive adequate energy to operate, the overall system must be sized through calculations due to find the optimum combination. This sizing will determine the amount of each component that needed in the system. The hardware is setup in front of CERE building which located at Kangar, Perlis, Malaysia. As the results from the calculation, the system required 6 units of PV module, 5 units of battery and a 0.23 kW inverter. The cable and protection devices are from the calculation. The entire system was successfully installed and was able to support the load demand.